SIMULATION OF THE BEHAVIOR OF THE WATER TABLE IN A COASTAL AQUIFER SYSTEM FINITE ELEMENT - Lara Romero, Luis (2016)
This paper presents the application of Galerkin method to discretize the model equation of groundwater ow in a conned aquifer semipermeable with tidal boundary conditions on one of itsborders, the other borders remain constant. For the simulations was generated a numerical program, Ground Water Finite Element Method, which implements the method of nite elements withtriangular elements with three nodes and a degree of freedom per node.